The Quality of Educational Services and Examining the Impact on Engineering Education - Sayyad, Shabnam; Sayyad, Farook; Ansari, Imran (Journal of Engineering Education Transformations, 2025)
Education is a fundamental aspect of human development, and the provision of high-quality educational services is critical for the success of individuals and societies. This manuscript examines the concept of quality in education and its impact on educational services. The manuscript begins by defining quality in education and exploring its various dimensions, including access, equity, relevance, effectiveness, and efficiency. It then examines the role of educational services in providing high-quality education, including curriculum design, teaching methods, assessment, and student support. The manuscript also discusses the challenges and opportunities for improving the quality of educational services, including the need for collaboration and innovation. Finally, the manuscript concludes by highlighting the importance of quality in education and the role of educational services in achieving this goal.